Does ranking stimulate government performance? Evidence from China’s key environmental protection cities - Liu, Lei; Yang, Zhaotian; Song, Suqin (Social indicators research, 2021)
With the air quality ranking of China’s Ministry of Ecology and Environment as a case, this paper examines whether the public ranking could stimulate the ranked cities to improve performance. The results show that the horizontal ranking, i.e., the relative position among the cities, significantly stimulates the cities to improve air quality. The stimulating effect is significant for all the three type of cities, i.e., cities with good, medium and poor air quality, and is the strongest for the cities with good air quality. However, the stimulating effect for air quality improvement is not enough to alter the air quality comparison among the cities. Compared to other cities, if a city is ranked relatively low in the last year, the air quality in the current year is still relatively poor. The inertia is particularly significant for the cities with poor air quality. The vertical ranking, i.e., if the rank of a city progresses or retrogresses, does not affect the air quality and air quality change of the city. Overall, public ranking is argued to stimulate performance improvement by seducing the competition among local governments, although the actual effect is still subject to the perception of local governments and their capacity to respond to the ranking.